Network Cooperation of Research Universities - Sobolewska , Olga; Waszkiewicz , Małgorzata (Management and Administration Journal, 2017)
The article presents the path of evolution followed by contemporary research institutions. Similarly to business organizations, colleges and universities also evolve toward better access to the broadly defined resources (both tangible and intangible) and development of scientific potential. Consequently, universities strive for a significant place in national and transnational economies. It is a task that requires them to introduce organizational changes. One of these changes, increasingly noticeable no less, is being open to cooperation and willingness to establish relationships based on cooperation. Technological advancement provides, in this regard, a number of solutions and facilities willingly applied by research institutions and their representatives. The authors of the publication, based on the conducted studies, point to the need of establishing cooperative relationships that exceed the boundaries of the organization and to the advantage of this solution in the implementation of scientific and research projects.(original abstract)